Revisiting the Formation of Creative Competences in the System of Engineering Education (Through the Example of “Creativity of Engineer” – Course Taught in National Research Tomsk Polytechnic University (Russia)); Innovation Management and Education Excellence Vision 2020: from Regional Development Sustainability to Global Economic Growth - Ardashkin I. B. Igor Borisovich; Vtorushin N. A. Nikolay Anatolievich; Gurieva I. Yu. Irina Yurievna; Shtanko M. A. Marina Aleksandrovna (2016, 2016)
Title screen